Financial Accounting - Johal, Parminder; Vickerstaff, Beverly (London : Hodder Education, 2012)
Clear, concise, and written by experts currently lecturing in the field, 'Financial Accounting' focuses exclusively on what you need to know for success in your business course and today's global economy.
Formerly CIP.
Includes bibliographical references and index.
Keywords: Accounting -- Textbooks